2012
DOI: 10.1007/s12070-011-0436-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of Foreign Bodies in the Aerodigestive Tract

Abstract: Foreign body (FB) aspiration and ingestion are frequently encountered by emergent otolaryngology services. The authors describe their experience in the management of FB cases in the aerodigestive tract. We carry a retrospective study about 626 patients who came or were referred to our department between 1996 and 2007 with a history or suspicion of a FB in the aerodigestive tract (except nasal and oropharyngeal FB). All of them have undergone rigid endoscopy under general anaesthesia. Children younger than 10 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 18 publications
0
30
1
Order By: Relevance
“…5,6,7 In this study it has been observed that foreign body esophagus is the most common indication for rigid endoscopy as 51.95% of the cases undergoing rigid esophagoscopy were due to ingestion of foreign body. Hariga et al 8 showed that most common indication for rigid endoscopy was foreign body in 87.7 % of their patients in contrast to our study where foreign body was the major indication but our percentage was low 62.85%. This may be due to a chance occurrence or due to more awareness in our part of the world.…”
Section: Discussioncontrasting
confidence: 93%
“…5,6,7 In this study it has been observed that foreign body esophagus is the most common indication for rigid endoscopy as 51.95% of the cases undergoing rigid esophagoscopy were due to ingestion of foreign body. Hariga et al 8 showed that most common indication for rigid endoscopy was foreign body in 87.7 % of their patients in contrast to our study where foreign body was the major indication but our percentage was low 62.85%. This may be due to a chance occurrence or due to more awareness in our part of the world.…”
Section: Discussioncontrasting
confidence: 93%
“…[7][8][9] In Africa and the Indian subcontinent, coins, meat boluses, and dentures are the most commonly expected FBs that could be ingested. [10,11] Since the pattern and profile of FB ingestion have not so far been reported anywhere from India, and also the unique pattern of UGIT FBs that was observed in our set up over some time in which there was a predominance of pins and needles compelled us to observe it in a prospective manner.…”
Section: Introductionmentioning
confidence: 83%
“…The type of FB also varies from country to country. [6][7][8][9][10][11] The pattern must also be changing from time to time as the readily available things also change from time to time and from place to place. Such observations are not published and perhaps not studied.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In our study, we had 37 cases of oesophageal foreign body and 31 cases in airway, in our exclusive study in paediatric age group The study group had 32 male children and 36 female children, differing from other studies, reason due to the short duration of study of 6 months. 6 The reason which was given in their study was due to the over active nature of the male babies as compared to the females.…”
Section: Discussionmentioning
confidence: 98%